The Analysis of the Central Kalimantan Tourism Development Plan Based on Ecotourism Policy Perspective - Bhayu Rhama (Policy & Governance Review, 2018)
Ecotourism globally has become an alternative to mass tourism to minimize environmental impacts, and at the same time, it is also useful to improve the living standards of local communities. The Central Kalimantan government also underpin ecotourism activities as a tourism focus and written it on its regional regulations. This study is a literature study to analyse RIPPARPROV (Rencana Induk Pengembangan Pariwisata Provinsi/Provincial Tourism Development Master Plan) of Central Kalimantan 2013-2028 with a conceptual approach from Hall and Jenkins by looking at how clearly the desired policy issues are set forth in regulations. The method of analysis uses qualitative-comparative methods, by exploring the main themes of the global concept of ecotourism (which are ecotourism definition, ecology, education, responsibility, awareness of conservation and economy of local communities) in the RIPPARPROV of Central Kalimantan 2013-2028. The results of the analysis show that the Central Kalimantan Provincial Government is still premature in an effort to develop ecotourism in its territory. This is indicated by the lack of explanation about ecotourism specifically the absence of a policy on tourist education, awareness and conservation participation by tourists. There is only a policy of improving the local economy which is very prominent in Central Kalimantan’s RIPPARPROV.